Changes in CO2 Emissions from Energy Use : A Multicountry Decomposition Analysis - Kojima, Masami (World Bank, Washington, DC, 2014)
The continued growth of global emissions of carbon dioxide (CO2) and their likely adverse effects on global warming are focusing debate on the contribution of various countries to total emissions and the comparability of efforts across countries in mitigating these emissions. This paper examines recent trends in CO2 emissions across countries at different levels of development and asks what has been contributing to the growth of emissions as well as to their moderation. The paper applies a decomposition analysis, an accounting methodology based on a log mean Divisia index, to analyze the change in CO2 emissions over a decade.